2021
DOI: 10.1007/s11274-021-03106-2
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal variations in the physiological profiles of streambed bacterial communities: implication of wastewater treatment plant effluents

Abstract: The e uents of wastewater treatment plants (WWTPs) represent a complex mixture of nutrients and toxic substances, thus, the potential exists for the e uents to signi cantly impact the biochemical characteristics and bacterial communities of the receiving water. We examined spatial and seasonal patterns, and the impact of e uents on microbial biomass, bacterial community structure, and metabolic diversity on a fourth-order stream. We took triplicate sediment samples at ve different locations along a 5,000m tran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
1
1
0
Order By: Relevance
“…Moreover, they show the impact of WWTP effluent on downstream microbial communities, which have shifted from the microbial structure found in the upstream sites to the microbial structure of the WWTP effluent. This result was expected, as other studies have also found WWTP effluent to have an impact on downstream microbial communities [93,136,139,169,171]. However, unlike our study, these studies only looked immediately downstream of the WWTP and not at the whole river.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Moreover, they show the impact of WWTP effluent on downstream microbial communities, which have shifted from the microbial structure found in the upstream sites to the microbial structure of the WWTP effluent. This result was expected, as other studies have also found WWTP effluent to have an impact on downstream microbial communities [93,136,139,169,171]. However, unlike our study, these studies only looked immediately downstream of the WWTP and not at the whole river.…”
Section: Resultssupporting
confidence: 68%
“…Several studies have shown that this impact results in a reduction in the alpha diversity in sites immediately downstream of WWTPs [129,137], while others have shown a change in the balance between autotrophic and heterotrophic bacteria [166]. Other studies detect no change in alpha diversity before and after the WWTP [167][168][169]. The apparent lack of impact on alpha diversity might be explained by the fact that, while micropollutants can negatively affect the abundance of certain taxa, nutrients can favor the growth of others [166].…”
Section: Resultsmentioning
confidence: 99%